Beans comsumption can contribute to the prevention of cardiovascular disease - Vieira, Nayane Maria [UNESP]; Peghinelli, Vinícius Vigliazzi [UNESP]; Monte, Marina Gaiato [UNESP]; Costa, Nara Aline; Pereira, Amanda Gomes [UNESP]; Seki, Marcos Mitsuo [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Elsevier, 2023)
Cardiovascular diseases (CVD) are the major cause of global mortality, accounting for 31% of deaths worldwide. Healthy eating habits based on the consumption of bioactive molecules present in plant-based diets can contribute to the prevention of CVD. In this context, the consumption of common beans (Phaseolus vulgaris L.) is relevant. There are several species of beans, all of which provide proteins, carbohydrates, dietary fiber, vitamins, minerals, and phenolic compounds. More recently, the complexity of phytochemical components has expanded, including the role of antinutritional factors in nutrient bioavailability and immune responses. Experimental and clinical studies have shown that the consumption of beans results in less food consumption, control of body weight, and improvement of metabolic biochemical parameters. Thus, the consumption of beans is associated with a decrease in CVD risk factors. To date, there have been no interventional studies assessing CVD outcomes, such as hospitalization, infarction, and mortality, in the context of bean consumption. Furthermore, studies on the effect of bean consumption on metabolomics and intestinal microbiota are lacking. The purpose of this review is to explore the nutritional properties of beans and discuss the main effects of the consumption of beans on cardiovascular health. In conclusion, eating habits based on the consumption of bioactive molecules present in beans can contribute to the prevention of cardiovascular disease. Furthermore, there is a large gap in the literature regarding the consumption of beans associated with clinical outcomes, such as hospitalization and mortality.
Keywords: Beans; Cardiovascular diseases; Eating habits; Mortality; Nutritional properties